Pseudomonas aeruginosa RTE4: A Tea Rhizobacterium With Potential for Plant Growth Promotion and Biosurfactant Production - Chopra, Ankita; Bobate, Shishir; Rahi, Praveen; Banpurkar, Arun; Mazumder, Pranab Behari; Satpute, Surekha (Frontiers in Bioengineering and Biotechnology, 2020)
Tea is an ancient non-alcoholic beverage plantation crop cultivated in the most part of Assam, India. Being a long-term monoculture, tea plants are prone to both biotic and abiotic stresses, and requires massive amounts of chemicals as fertilizers and pesticides to achieve worthy crop productivity. The rhizosphere bacteria with the abilities to produce phytohormone, secreting hydrolytic enzyme, biofilm formation, bio-control activity provides induced systemic resistance to plants against pathogens. Thus, plant growth promoting rhizobacteria. represents as an alternative candidate to chemical inputs for agriculture sector. Further, deciphering the secondary metabolites, including biosurfactant (BS)allow developing a better understanding of rhizobacterial strains. The acidic nature of tea rhizosphere is predominated by Bacillus followed by Pseudomonas that enhances crop biomass and yield through accelerating uptake of nutrients. In the present study, a strain Pseudomonas aeruginosa RTE4 isolated from tea rhizosphere soil collected from Rosekandy Tea Garden, Cachar, Assam was evaluated for various plant-growth promoting attributes. The strain RTE4 produces indole acetic acid (74.54 µg/ml), hydrolytic enzymes, and solubilise tri-calcium phosphate (46 µg/ml). Bio-control activity of RTE4 was recorded against two foliar fungal pathogens of tea (Corticium invisium and Fusarium solani) and a bacterial plant pathogen (Xanthomonas campestris). The strain RTE4 was positive for BS production in the preliminary screening. Detailed analytical characterization through TLC, FTIR, NMR and LCMS techniques revealed that the strain RTE4 grown in M9 medium with glucose (2 % w/v) produce di-rhamnolipid BS. This BS reduced surface tension of phosphate buffer saline from 71 to 31 mN/m with a critical micelle concentration of 80 mg/L. Purified BS of RTE4 showed minimum inhibitory concentration of 5, 10 and 20 mg/ml against X. campestris, F. solani and C. invisium, respectively. Capability of RTE4 BS to be employed as a biofungicide as compared to Carbendazim - commercially available fungicide is also tested. The strain RTE4 exhibits multiple plant growth promoting attributes along with production of di-rhamnolipid BS. This gives a possibility to produce di-rhamnolipid BS from RTE4 in large scale and explore its applications in fields as a biological alternative to chemical fertilizer.